Stitching Sustainability: Phulkari as a Model for Tradition-based Women’s Enterprises (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper explores the dynamic intersection of traditional knowledge systems and women-led entrepreneurship through a case study of Phulkari, the iconic embroidery art form of Punjab. Rooted in the cultural and social fabric of Punjabi life since the 15th century, Phulkari has historically been practiced by women to commemorate significant life events, transmitted through generations via oral and experiential traditions. The study traces Phulkari’s evolution from a domestic and ritualistic craft to a commercially viable industry, examining how this transformation has opened new avenues for women of rural and semi-urban areas to engage in entrepreneurship. Women artisans in the 21st century, through cooperatives, Self-Help Groups (SHGs), and digital platforms such as Amazon Karigar and GoCoop, have leveraged Phulkari not only as a means of socio-cultural reclamation and innovation but also as a sustainable source of income. This paper also discusses the critical challenges faced by the sector, including limited market access, exploitation by intermediaries, digital illiteracy, and the erosion of authenticity due to mass production, all at their times. To combat these, the Geographical Indication (GI) tag was awarded to Phulkari in 2009 is evaluated as a potential tool for safeguarding community intellectual property. The study argues that Phulkari-based women’s entrepreneurship serves as a replicable model for inclusive and sustainable development, proving how indigenous traditions can be harnessed for both economic empowerment and cultural preservation.